Improved wet granulation techniques - Monika Pastewska; Wiesław Sawicki (Polish Pharmaceutical Society, 2020)
Wet granulation is one of the most frequently used processes in the pharmaceutical industry to manufacture solid dosage forms. Wet granulation is helpful in tableting active substances that are not susceptible to the compression. Despite many years of using this method in the production of drugs, the pharmaceutical industry prefers to use high-shear granulation and fluid bed granulation. Fluidized bed granulation can be very difficult. Problems can be related with apparatus, properties of the processed material, process parameters and transfer of the process on a larger scale. The undesirable variations that occur during application of the fluid bed granulation or high-shear granulation result mainly from the use of significant amounts of liquid. Alternative granulation methods can eliminate this problem by using smaller amounts of liquid during the process. Some of them, such as MADG and TAG granulation, thanks to the use of small amounts of them, allows to completely skip the drying stage. Melt granulation allows formation of granules without use of water, so the drying stage is not necessary as well. Another advantage is the reduction of variations in the nucleation of the granules as is the case in reverse phase granulation. Achieving an even distribution of water vapor on the powder particles in steam granulation initiates the granulation mechanism better than in traditional wet granulation. This contributes to the formation of highly porous granules with an even grain size distribution. In freeze granulation it is possible to obtain granules with a size strictly controlled by the spray parameters. Due to its excellent control of particle size and aerodynamic properties, this technique is helpful in producing powders that will be dispensed using inhalers. All these advantages resulting from the use of alternative granulation methods offer much more possibilities in the production of solid dosage forms. The qualitative properties of the granulate obtained in these processes do not differ significantly from the standards, and in some cases are even better than the properties of the granulate made with the use of high-shear granulation or fluidized bed granulation.